The Punicalagin Metabolites Ellagic Acid and Urolithin A Exert Different Strengthening and Anti-Inflammatory Effects on Tight Junction-Mediated Intestinal Barrier Function In Vitro - Hering, Nina A.; Luettig, Julia; Jebautzke, Britta; Schulzke, Jörg D.; Rosenthal, Rita (Frontiers in Pharmacology, 2021)
Scope: Ellagitannins are polyphenols found in numerous fruits, nuts and seeds. The elagitannin punicalagin and its bioactive metabolites ellagic acid and urolithins are discussed to comprise a high potential for therapeutically or preventive medical application e.g. in intestinal diseases. The present study characterizes effects of punicalagin, ellagic acid and urolithin A on intestinal barrier function in the absence or presence of the proinflammatory cytokine tumor necrosis factor-α (TNFα). Methods and Results: Transepithelial resistance (TER), fluorescein and ion permeability, tight junction protein expression and signalling pathways were examined in Caco-2 and HT-29/B6 intestinal epithelial cell models. Punicalagin had less or no effects on barrier function in both cell models. Ellagic acid was most effective in ileum-like Caco-2 cells, where it increased TER and reduced fluorescein and sodium permeabilities. This was paralleled by myosin light chain kinase 2 mediated expression down-regulation of claudin-4, -7 and -15. Urolithin A impeded the TNFα-induced barrier loss by inhibition of claudin-1 and -2 protein expression upregulation and claudin-1 delocalization in HT-29/B6. Conclusion: Ellagic acid and urolithin A affect intestinal barrier function in distinct ways. Ellagic acid acts preventive by strengthening the barrier per se, while urolithin A protects against inflammation-induced barrier dysfunction.